CITRA MEREK DAN HARGA DALAM KEPUTUSAN PEMBELIAN YANG DILAKUKAN KONSUMEN - Tiris Sudrartono; Muthmainnah (POLITEKNIK PIKSI GANESHA, 2022)
This study was conducted to determine the effect of brand image and price on consumer purchasing decisions at PT. XYZ Bandung. The method used is quantitative and descriptive, the results of the study are known the magnitude of the effect of the brand image on purchasing decisions of 37.9, the remaining 62.1% is influenced by other factors. The magnitude of the effect of prices on consumer purchasing decisions is 68.0, the remaining 32.0 is influenced by other factors. This means that there is a magnitude of the influence of 68.7 brand images and prices on consumer purchasing decisions, the remaining 31.3 is influenced by other factors. To improve purchasing decisions through brand and price imagery, PT. XYZ is advised to provide colors of clothing with bright colors such as pastel colors to attract consumers, provide daily discount programs and annual discount programs by maximizing potential on social media and promoting products by influenceres by creating video tutorials or video reviews in detail reviews product Keywords: Brand Image, Price, Purchase Decision